2017
DOI: 10.3390/v9070175
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 as a New Regulator of HPV16 Transcription

Abstract: Persistent infections with high-risk human papillomavirus (HPV) constitute the main risk factor for cervical cancer development. HPV16 is the most frequent type associated to squamous cell carcinomas (SCC), followed by HPV18. The long control region (LCR) in the HPV genome contains the replication origin and sequences recognized by cellular transcription factors (TFs) controlling viral transcription. Altered expression of E6 and E7 viral oncogenes, modulated by the LCR, causes modifications in cellular pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…The LCR displayed greater sequence variability than any other region in the HPV16 genome, which was consistent with our results showing that the nucleotide variation rate of LCR was 8.17%. This region includes several binding sites for cellular and viral TFs, which regulate the replication of HPV16 and the transcriptional activity of the early regions . In the present study, 25 loci identified in the LCR of the various sequences are embedded in the putative binding sites for transcription factors TBP, Ftz, USF, Hb, Oct‐1, C/EBP α, GR_α, YY1, AP‐1, NF‐1, Pit‐1α, E2, and ICSBP.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The LCR displayed greater sequence variability than any other region in the HPV16 genome, which was consistent with our results showing that the nucleotide variation rate of LCR was 8.17%. This region includes several binding sites for cellular and viral TFs, which regulate the replication of HPV16 and the transcriptional activity of the early regions . In the present study, 25 loci identified in the LCR of the various sequences are embedded in the putative binding sites for transcription factors TBP, Ftz, USF, Hb, Oct‐1, C/EBP α, GR_α, YY1, AP‐1, NF‐1, Pit‐1α, E2, and ICSBP.…”
Section: Discussionmentioning
confidence: 62%
“…Notably, the harmful behaviors of HPV‐positive cancer cells was greatly determined by the expression of the E6 and E7 oncogenes, but by influencing their normal biological processes it was principally reversible . The LCR contains the replication origin and cis‐responsive elements recognized by cellular and viral TFs controlling viral transcription . Therefore, we systematically analysed the genetic variability and population genetics of HPV16, nucleotide sequence, amino acid sequence, and structure of E6 and E7 genes, and prediction of transcription factor binding sites in the LCR .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, upon bacterial DNA stimulation, Sox2 interacts with TAB2, which causes the TAB2/TAK1 kinase complex to dimerize and lead to the activation of NF-κB and AP-1 signaling. A recent study analyzed the long control regions, which are important sites of viral replication regulation for HPV16, and found that overexpression that Sox2 can repress the E6 and E7 oncogene expression of HPV16 (Martínez-Ramírez et al, 2017). Although this study did not investigate innate immune induction by Sox2, this study highlights the role of Sox2 in mediating a DNA virus infection and will need further investigation to clarify its mechanism.…”
Section: Intracellular Recognition Of Dnamentioning
confidence: 99%
“…Some investigators found that SOX2 regulated HPV16 transcription by inhibiting activity of its long control region and finally decreasing expression of the E6 and E7 oncogenes in CC carcinogenesis 64 . Furthermore, mounting evidence implicated other members of the SOX genes family in the regulation of CC progression ( Figure 5 ) and identified their roles as biomarkers for predicting the prognosis of patients with CC ( Table 1 ).…”
Section: Sox Genes In Gcsmentioning
confidence: 99%